Geotourism Potential and Challenges of the Coastal Region Around Santa Marta (Colombia): a Novel Strategy for Socioeconomic Development - Carlos Alberto Ríos-Reyes; Dino Carmelo Manco Jaraba; Oscar Mauricio Castellanos-Alarcón (Cuadernos de Geografía: Revista Colombiana de Geografía, 2021)
This research article refers to the coastal region around Santa Marta (Colombia), showing a valuable geodiversity from a coastal geomorphology point of view, with great scientific importance for the study of coastal landscapes and attractive for the development of geotourism. The landscape value of the coastal regions of the Colombian Caribbean, in particular of the coastal region around Santa Marta, should be globally recognized to improve and protect its aesthetic and environmental value through geoeducation and geotourism activities that contribute to its geoconservation, motivating efficient management that outlines guidelines that promote the development of appropriate tourist infrastructure, centers of scientific interpretation, dissemination and educational materials, active exchange with geoparks, continuous improvement, and participation of local communities.